Teologie en konteks: vraag na 'n teologie vir Suid-Afrika - R. Venter (Acta Theologica)
This article addresses what it implies to do theology with a “sense of place”. The question is raised about a responsible theology for South Africa and it is situated methodologically within the contemporary imperative of considering “context” as a major source for theology. The article acknowledges various theological attempts at taking the South African reality seriously. The central argument of the article consists of three moves. A suggestion is given as to what might constitute “responsible theology”; a brief profile presents the multifaceted character of the present South African horizon, and a constructive proposal stresses hermeneutical revisionings of Trinitarian theology, soteriology (Gospel), ecclesiology (identity and community), and spirituality.